Introduction to Financial Accounting - Annand, David; Dauderis, Henry; Open Textbook Library (Open Textbook Library, 2017)
This textbook is an adaptation by Athabasca University of the original text written by D. Annand and H. Dauderis. It is intended for use in entry-level college and university courses in financial accounting. A corporate approach is utilized consistently throughout the book. The adapted textbook includes multiple ancillary student and instructor resources. Student aids include solutions to all end-of-chapter questions and problems, and randomly-generated spreadsheet problems that cover key concepts of each chapter. These provide unlimited practice and feedback for students. Instructor aids include an exam bank, lecture slides, and a comprehensive end-of-term case assignment. This requires students to prepare 18 different year-end adjusting entries and all four types of financial statements, and to calculate and analyze 16 different financial statement ratios. Unique versions can be created for any number of individual students or groups. Tailored solutions are provided for instructors. The original Annand/Dauderis version of the textbook including .docx files and ancillary material remains available upon request to D. Annand (davida@athabascau.ca).
Introduction to Financial Accounting -- The Accounting Process -- Financial Accounting and Adjusting Entries -- The Classified Balance Sheet and Related Disclosures -- Accounting for the Sale of Goods -- Assigning Costs to Merchandise -- Cash and Receivables -- Long-lived Assets -- Debt Financing: Current and Long-term Liabilities -- Equity Financing -- The Statement of Cash Flows -- Financial Statement Analysis -- Proprietorships and Partnerships
In English.
Description based on print resource
Keywords: Finance -- Textbooks; Accounting -- Textbooks; Business -- Textbooks